2022
DOI: 10.1111/evo.14410
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐related differences in aging rate are associated with sex chromosome system in amphibians

Abstract: Sex‐related differences in mortality are widespread in the animal kingdom. Although studies have shown that sex determination systems might drive lifespan evolution, sex chromosome influence on aging rates have not been investigated so far, likely due to an apparent lack of demographic data from clades including both XY (with heterogametic males) and ZW (heterogametic females) systems. Taking advantage of a unique collection of capture–recapture datasets in amphibians, a vertebrate group where XY and ZW system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 54 publications
2
9
0
Order By: Relevance
“…An analysis focused on tetrapods suggested that the sex‐determination system (XY vs. ZW) explained ¼ to ⅓ of the differences in the adult sex ratio (a proxy of sex differences in adult mortality) observed between species, depending on the heterogametic sex (Pipoly et al, 2015 ). A similar result was obtained in a study focused on amphibians (Cayuela et al, 2021 ). Data from the four core genotypes in mouse (animals with either XX or XY sex chromosome complement and either ovaries or testes generated by exploiting a translocation of the SRY gene to an autosome) shows that the presence of two X chromosomes improves lifespan, irrespective of the gonads (Davis et al, 2019 ).…”
Section: Genomic Differences Between the Sexes And Differences In Agingsupporting
confidence: 88%
“…An analysis focused on tetrapods suggested that the sex‐determination system (XY vs. ZW) explained ¼ to ⅓ of the differences in the adult sex ratio (a proxy of sex differences in adult mortality) observed between species, depending on the heterogametic sex (Pipoly et al, 2015 ). A similar result was obtained in a study focused on amphibians (Cayuela et al, 2021 ). Data from the four core genotypes in mouse (animals with either XX or XY sex chromosome complement and either ovaries or testes generated by exploiting a translocation of the SRY gene to an autosome) shows that the presence of two X chromosomes improves lifespan, irrespective of the gonads (Davis et al, 2019 ).…”
Section: Genomic Differences Between the Sexes And Differences In Agingsupporting
confidence: 88%
“…Two additional observations imply that the unguarded X is unlikely to provide a general explanation for sex differences in longevity. First, extensive sex differences for ageing and life span are observed in species with largely homomorphic sex chromosomes, including higher mortality rates in the heterogametic sex (Cayuela et al 2022), which cannot be explained by unguarded X effects. Second, although birds are predicted (by unguarded X theory) to exhibit stronger sex differences in life span than mammals, data support the opposite pattern (the sex difference in life span in birds is roughly half the average difference observed in mammals; Lemaître et al 2020;Xirocostas et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…2020; Cayuela et al. 2022). Estimates of adult sex ratios are typically skewed toward the homogametic sex (i.e., females in species with X chromosomes; males in species with a Z; Pipoly et al.…”
mentioning
confidence: 99%
“…Heterogamety is a fundamental aspect of organismal biology that, according to recent research, has far‐ranging consequences on life histories and population dynamics, including sex ratios, sex‐specific aging rates, and life spans. [ 82–84 ] Here we have highlighted that heterogamety may further influence the fate of ectothermic vertebrates by affecting their propensity to undergo environmental sex reversal. By considering “asymmetrical sex reversal,” a relaxed interpretation of Witschi's rule, we can generate testable predictions regarding the differences in sex‐reversal propensity between populations with different sex‐chromosome systems induced by different environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Heterogamety is a fundamental aspect of organismal biology that, according to recent research, has far-ranging consequences on life histories and population dynamics, including sex ratios, sex-specific aging rates, and life spans. [82][83][84] Here we have highlighted that heterogamety may further influence the fate of ectothermic vertebrates by affecting their propensity to undergo environmental sex reversal.…”
Section: Discussionmentioning
confidence: 99%